2016
DOI: 10.1177/0038040715627196
|View full text |Cite
|
Sign up to set email alerts
|

New Horizontal Inequalities in German Higher Education? Social Selectivity of Studying Abroad between 1991 and 2012

Abstract: On the basis of theories of cultural reproduction and rational choice, we examine whether access to study-abroad opportunities is socially selective and whether this pattern changed during educational expansion. We test our hypotheses for Germany by combining student survey data and administrative data on higher education entry rates. We find that studying abroad was socially selective during the entire observation period. Selectivity increased between 1991 and 2003 and hardly changed thereafter. Unexpectedly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 38 publications
5
65
0
4
Order By: Relevance
“…Therefore, students with more advantageous socioeconomic background (higher parental education and higher family income) tended to study in a more prestigious university during the SWB programme. The finding corroborates with the results found by Netz and Finger (2016) regarding international mobility during H.E. expansion in Germany.…”
Section: Inequality Withinsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, students with more advantageous socioeconomic background (higher parental education and higher family income) tended to study in a more prestigious university during the SWB programme. The finding corroborates with the results found by Netz and Finger (2016) regarding international mobility during H.E. expansion in Germany.…”
Section: Inequality Withinsupporting
confidence: 92%
“…Salisbury et al (2008) showed that undergraduate students in the USA with parents with higher educational attainment, who were more interested in reading and more open to diversity, were more likely to plan to study abroad at the beginning of their freshman year. Netz and Finger (2016), examining the changes in inequality in access to and within international mobility programmes during the expansion of H.E. in Germany, showed that the effect of parental education on the likelihood of participating in international mobility increased between 1991 and 2003 but remained constant and significant after 2003.…”
Section: Research On International Student Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research stresses that ISM is subject to (self-)selection. Various studies show that a high social background is positively associated with ISM (Wiers-Jenssen 2011;Kratz 2012;Hauschildt et al 2015;Netz and Finger 2016). Besides, better marks at secondary school (Wiers-Jenssen 2011) and mobility prior to higher education entry (Lörz, Netz, and Quast 2015) are associated with a higher ISM propensity.…”
mentioning
confidence: 99%
“…Moving beyond micro-and macro-economic explanations (e.g. by Hemming et al, 2016;Netz & Finger, 2016;Ohnmacht et al, 2009) this comparative work sheds light on the individual sphere of the heterogeneity of the phenomenon of the mobility of European youth. It explores the variety of young people's mobility-related action by contextualising them according to their institutional and biographical settings.…”
Section: Summary and Discussionmentioning
confidence: 85%